Parlay and OGSA based framework for service creation in NGN - LIU Zhen1; YANG Jing 2; LI Guo-jie2; ZHANG Guo-qing2 (Tongxin xuebao)
A parlay and open grid services architecture（OGSA） based framework for service creation in NGN was pro-posed,which not only provided uniform access to heterogeneous network capabilities,but also built effective distributed convergence mechanisms beyond them.Then a service-oriented method for communication between Parlay and OGSA was further proposed.It was a new and significant attempt to apply grid technologies to telecommunication service crea-tion.The validity of the proposed framework for flexible service creation spanning heterogeneous networks is verified by simulations.Moreover,the proposed framework can support legacy communication terminals without upgrading on cli-ent.